Faktor-Faktor yang Berhubungan dengan Kepatuhan Monitoring Early Warning Score (EWS) di Ruang Rawat Inap Rumah Sakit X Kota Tarakan - Alfianur; Safitri, Andini; Lesmana, Hendy; Kartanti, Natalia Ida (Pustaka Galeri Mandiri, 2026)
Early Warning Score (EWS) is a system designed to detect early clinical deterioration in patients through the monitoring of vital signs. Although EWS has been implemented at Hospital X in Tarakan City, its implementation has not yet been fully optimal. Nurses’ compliance in conducting EWS monitoring may be influenced by several factors, including knowledge, training, and workload. This study aimed to determine the relationship between nurses’ knowledge, training, and workload and their compliance with EWS monitoring in the inpatient wards of Hospital X, Tarakan City. This research employed a quantitative approach with a cross-sectional design. A total of 49 nurses were selected using total sampling technique. The instruments used were questionnaires and observation sheets. Data were analyzed using the Gamma statistical test. The results showed that the majority of respondents had good knowledge (85.7%), had attended EWS training (71.4%), and demonstrated a high level of compliance in EWS monitoring (95.9%). Most respondents also perceived a high mental workload (63.3%). The Gamma test results indicated that there was no significant relationship between knowledge (p = 0.182), training (p = 0.153), and workload (p = 0.885) and compliance with EWS monitoring. In conclusion, knowledge, training, and workload were not significantly associated with nurses’ compliance in monitoring the Early Warning Score. Other approaches are needed to improve compliance, such as routine supervision, evaluation of EWS implementation, and improvement of the documentation system.